Determination of branched chain fatty acids in plasma of type 2 diabetics - Laštovička, Petr; Čermák, Tomáš; Hájek, Filip; Líbalová, Martina; Nováková Mužáková, Vladimíra; Skalický, Jiří; Čegan, Alexander (University of Pardubice, 2016)
Insulin resistance in type 2 diabetic patients reduces activation of PPAR, which may lead to accumulation of branched-chain fatty acids, as well as saturated fatty acids, when natural sources of these fatty acids are dairy products. The aim of our study was to verify whether or not the accumulation of the branched chain fatty acids takes place in type 2 diabetes and, if so, to specify the corresponding lipid fraction. Totally 23 anonymised plasma samples of type 2 diabetic patients had been collected and subsequently divided by glycosidic haemoglobin levels into two groups of 11 compensated and 12 decompensated; the plasma of 10 healthy blood donors being further processed. At first, the samples were divided into particular lipid classes using thin layer chromatography. Then, we set the content of individual fatty acids in all lipid classes using gas chromatography. The results were calculated and evaluated statistically by applying the SigmaStat 3.5 program. It has been found that the most abundant branched chain fatty acid is 14-methylhexadecanoic acid as statistically significant increase of this acid was found in both compensated diabetics (p # 0.001) and decompensated ones (p # 0.001) in comparison with controls. The 14-methylhexadecanoic acid was ascertained in the diacylglycerol fraction, as well as in free fatty acid fraction of the compensated (p = 0.008) and decompensated (p = 0.007) diabetics. Furthermore, an increase in the content of branched-chain fatty acids in diabetic patients has been proved. An accumulation of these substances in diabetics thus raises a question on their actual effect on the human organism.